Digital triage forensics : processing the digital crime scene - Pearson, Stephen, 1963- (Syngress, 2010)
"Digital Triage Forensics (DTF) is a procedural model for the investigation of Digital Crime Scenes including both Traditional Crime Scenes and the more complex Battlefield Crime Scenes. The United States Army and other traditional Police agencies use this model for current Digital Forensic Applications. The tool, training, and techniques from this practice are being brought to the public in this book for the first time. Now Corporations, Law Enforcement, and Consultants can benefit from the unique perspectives of the experts who coined 'Digital Triage Forensics'."--Resource description page.